2004
DOI: 10.1111/j.1365-4632.2004.02244.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases in Turkish renal transplant recipients

Abstract: In this study, we observed that cutaneous lesions, especially those caused by infectious diseases, had a higher frequency in RTRs. The findings emphasize the importance of regular dermatological screening in these patients, which can provide early diagnosis and a better quality of life for RTRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
3
15
1
Order By: Relevance
“…The risk of skin lesions in RTRs has been frequently described; however, it differs markedly by ethnic groups, skin type, and geographical location (3, 4). On the other hand, few reports deal with case–control studies of skin infections in RTRs (5, 6).…”
mentioning
confidence: 99%
“…The risk of skin lesions in RTRs has been frequently described; however, it differs markedly by ethnic groups, skin type, and geographical location (3, 4). On the other hand, few reports deal with case–control studies of skin infections in RTRs (5, 6).…”
mentioning
confidence: 99%
“…More recently, Abdelaziz et al [7] reported a lower prevalence in Egyptian patients (7.6%), but in this case, the prevalence was significantly higher than that of healthy control individuals (2.3%). In contrast, Gulec et al [9] and Alper et al [31] reported higher OM rates in Turkish patients (respectively 12.7 and 12.4%). However, in the study of Gulec et al [9], the rate was similar to that in the control group, whereas in the study of Alper et al [31], it was significantly higher.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, Gulec et al [9] and Alper et al [31] reported higher OM rates in Turkish patients (respectively 12.7 and 12.4%). However, in the study of Gulec et al [9], the rate was similar to that in the control group, whereas in the study of Alper et al [31], it was significantly higher. The difference in rates between these stud- Table 6.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a systematic overview made in Leiden, 591 nonmalignant skin diseases were registered in 1768 (33%) organ transplant recipients followed over 13 years [1]. Smaller series reported that the prevalence of nonmalignant skin lesions in transplant recipients may range between 49% and 87% [2–5]. The lesions are mainly related to the prolonged use of immunosuppressive drugs, but an important contributing role may also be played by exposure to sunlight and viral infections.…”
mentioning
confidence: 99%